Pengaruh Pembelajaran Pendidikan Agama Islam Terhadap Kesadaran Spiritual Siswa Kelas XI di SMK Pasundan 4 Bandung - Ilyas Abdul Latif; Siti Lutfiani Nurlatifah Dahlan; Suci Rahmawati Mustopa; Muhsin Muhsin; Afrizal Khairurrohman (Tarbiatuna: Journal of Islamic Education Studies, 2024)
This research aims to analyze the influence of Islamic Education learning on the spiritual awareness of 11th-grade students at SMK Pasundan 4 Bandung. The research method used is a qualitative approach with a descriptive qualitative method. Data collection was conducted through interviews with Islamic Education teachers and 11th-grade students. The results of the study indicate that the portrayal of spiritual behavior among students at SMK Pasundan 4 Bandung is still not optimal, with some behaviors lacking discipline, politeness, and honesty. Efforts by Islamic Education teachers to enhance students' spiritual awareness are carried out through planning, implementation, and evaluation of learning by applying Discovery Learning, Project Based Learning, and Problem Based Learning models. The supporting factor for Islamic Education learning is adequate school facilities, while the inhibiting factor is some students who underestimate Islamic Education lessons and often skip classes. The conclusion of this study is that Islamic Education learning has not fully influenced the spiritual awareness of students at SMK Pasundan 4 Bandung. More intensive efforts are needed from teachers and the school to enhance students' spiritual awareness through the habituation of religious activities and exemplary behavior.